Perancangan Buku Ilustrasi Digital Painting “Culinary Experience Of Malang” Sebagai Upaya Mendukung Potensi Kuliner Legendaris Di Kota Malang - Fery Andry Asmawan (MAVIS : Jurnal Desain Komunikasi Visual, 2019)
Malang is one of the major cities in Indonesia which has a lot of potential, including the culinary and tourism potential. Until now, local culinary already exists since a long time is still not able to compete with emerging new culinary. Therefore, the author makes a book illustration digital painting that contains about a legendary culinary places in the city of Malang. The illustration is chosen because the illustration is a picture that communicates a concept or message. The best medium to enjoy the illustrations are on the media-the media designation, such as magazines, books, etc. Digital painting provides convenience in terms of technical illustration creation. The design model using the SadjimanEbdiSanyoto model, that begins with the background of the problem, identification, data source, and then resumed the synthesis, concept design, design process, and the final design. The software used in the process of creating digital illustrations include: Adobe Photoshop CS and Adobe Illustrator CS 6. The book that made measuring 21 cm x 21 cm use Art Paper 310 g on book covers and 120 grams on the contents of the book, volume using volume spiral. Media supporters include brochures, posters, merchandise, social media, mug, tote bag, and bookmarks. For subsequent authors are expected to design with the same problems but with different media.